Riding attention spikes: How analysts respond to advertising - Koo, Minjae; Wang, Annika Yu; Wang, Yin; Zhang, Liandong (Contemporary Accounting Research, 2025)
Abstract Product market advertising, while containing little new information, triggers spikes in investor attention. Using weekly advertising data, we find that sell‐side analysts issue optimistic earnings forecasts in response to heavier advertising in the prior week. This effect is not driven by confounding earnings or product news. It is more pronounced for experienced analysts and analysts affiliated with brokerages that rely solely on trading revenues. The optimistic forecast bias intensifies the impact of advertising on investor trades of the underlying stock during the following week, especially on retail buying. Overall, analysts appear to issue optimistic forecasts to exploit retail investor attention spikes induced by advertising.